The study of EMG signals during sitting postures in Muslim prayer - Harun, H.; Mohd Nasir, N. F.; Salleh, A. F. (2016 IEEE EMBS Conference on Biomedical Engineering and Sciences (IECBES), 2016)
Electromyography (EMG) signals at the lower limb muscles on static posture of sitting during solat had been studied based on the sayings of Prophet Muhammad (hadiths) about this particular posture. Gastrocnemius and Tibialis Anterior were the chosen muscles as both are the major muscles of the lower leg. A group of 10 subjects had participated in this study. The EMG data signal results were analyzed statistically using the Paired-Samples T Test. The statistical results showed that Sitting of Tawarruk has better EMG level on lower limb muscles than Sitting of Iftirasy while Paired-Samples T Test shows that there are no significant differences between both Sittings at the Right Gastrocnemius, Right Tibialis Anterior and Left Tibialis Anterior muscles during the postures. However, there is a significant different on Left Gastrocnemius muscles based on the EMG results for both postures. This significant different on the Left Gastrocnemius is due to the stabilization of the muscles activities for both sides of leg during the sitting postures. Thus, these postures showed by the Prophet Muhammad SAW during the solat should not have adverse effect to the lower muscles studied.